Manajemen Mutu Transportasi Laut: Studi pada Upaya Peningkatan Standar Keselamatan dan Kenyamanan Penumpang - ardila, septia; Riyadi, Slamet (Politeknik Pelayaran Sumatera Barat, 2025)
Maritime transportation plays a vital role in supporting connectivity between the island regions of Indonesia, which consists of more than 17,000 islands. However, there are still challenges related to service quality, particularly in terms of passenger safety and comfort. On the other hand, passenger comfort still faces gaps, especially regarding the availability of basic facilities such as decent waiting rooms, adequate sanitation, and accessibility for persons with disabilities. This article aims to analyze the implementation of quality management in maritime transportation through a literature study of related journals and research reports. The findings of the study indicate that the application of quality management standards based on the International Organization for Standardization (ISO), improvement of Human Resources (HR) quality, and the utilization of digital technology are key to enhancing navigational safety and passenger comfort. This quality management effort also has a positive impact on public trust, operational efficiency, and the competitiveness of Indonesia's maritime transport at both regional and global levels. Overall, this study emphasizes that the success of improving maritime transport quality is influenced by four main factors: the implementation of international quality standards, strengthening human resources (HR) capacity, enhancement of comfort facilities, and the utilization of digital technology innovations. The integrated implementation of quality management is expected to realize a safe, comfortable, efficient, and globally competitive Indonesian maritime transport, while also strengthening its role as the backbone of national maritime connectivity.